(untitled) (Baghdad Science Journal, 2015)
The present study designed to determine the ethanolic extract of Cyperus rotundus on Liver in Albino Male Mice . In the present study 18 Male mice were used they divided into six groups ( 1st group consedered control group , 2nd group injected by 250 mg/ml from extract , 3th group injected by 300 mg/ml from extract , 4th group injected by 350 mg/ml from extract , 5th group injected by 400 mg/ml from extract and the 6th group injected by 450 mg/ml from extract ) . the expermint lasted for two days and the doses gived by intraperitonial injection . showed from the study results that ethanolic extract for Cyperus rotundus have negative effect on Liver tissue in 250 , 300 , 350 mg/ml concentrations when comparsion with control group . the results from two last groups was the same effect to the first three groups but was more negative on Liver tissue from the first three groups treated . We concluded from the present results that ethanolic extract from rhizomes of Cyperus rotundus have negative effect on liver tissue in the different concentrations .